Biosimilars in immune‐mediated inflammatory diseases: initial lessons from the first approved biosimilar anti‐tumour necrosis factor monoclonal antibody. (25th September 2015) - Isaacs, J. D.; Cutolo, M.; Keystone, E. C.; Park, W.; Braun, J.
Abstract: The introduction of targeted biological therapies has revolutionised the management of immune‐mediated inflammatory diseases (IMIDs) such as rheumatoid arthritis, ankylosing spondylitis, psoriasis and inflammatory bowel disease. Following treatment with these therapies, many patients experience significant improvements in different aspects of their disease, including symptoms, work productivity and other outcomes relevant for individuals and society. However, due to the complexity of biological drug development and manufacturing processes, the costs of these therapies are relatively high. Indeed, the financial burden on healthcare systems due to biological therapies is considerable and lack of patient access to effective treatment remains a concern in many parts of the world. As many reference biological therapies have now reached or are near to patent expiry, a number of 'biosimilar' drugs have been developed for use in various clinical settings, and some of these drugs are already in use in several countries. While the potential pharmacoeconomic benefits of cost‐effective biosimilars seem clear, several issues have been raised regarding, for example, the definition of biosimilarity and the validity of indication extrapolation, as well as the 'switchability' and relative immunogenicity of biosimilars and their reference drugs. In this review, these issues will be discussed with reference to CT‐P13, a biosimilar of the anti‐tumour necrosis factor monoclonal antibody infliximab, which is approved in Europe and elsewhere for the treatment of various IMIDs. Other important issues, including those related to data collection during nonclinical and clinical development of biosimilars, are also discussed.